Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1086/344191
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics ofStreptococcus pneumoniaeand Atypical Bacterial Infections in Children 2–5 Years of Age with Community‐Acquired Pneumonia

Abstract: The characteristics of community-acquired pneumonia associated with Streptococcus pneumoniae infection were compared with those associated with atypical bacterial infection and with mixed S. pneumoniae-atypical bacterial infection in 196 children aged 2-5 years. S. pneumoniae infections were diagnosed in 48 patients (24.5%); atypical bacterial infections, in 46 (23.5%); and mixed infections, in 16 (8.2%). Although white blood cell counts and C-reactive protein levels were higher in patients with pneumococcal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
2
12

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 51 publications
7
57
2
12
Order By: Relevance
“…Recently published data have confirmed the prevalence of atypical pathogens in paediatric CAP patients [66], highlighting their significant role in the pathogenesis of the disease and the need to reassess antibiotic therapy with b-lactam agents. In 196 children with CAP aged 2-5 yrs, S. pneumoniae infections were diagnosed in 24.5% of patients, atypical bacterial infections in 23.5% of patients, and mixed S. pneumoniae and atypical bacterial infections in 8.2% of children.…”
Section: Community-acquired Pneumoniamentioning
confidence: 92%
See 1 more Smart Citation
“…Recently published data have confirmed the prevalence of atypical pathogens in paediatric CAP patients [66], highlighting their significant role in the pathogenesis of the disease and the need to reassess antibiotic therapy with b-lactam agents. In 196 children with CAP aged 2-5 yrs, S. pneumoniae infections were diagnosed in 24.5% of patients, atypical bacterial infections in 23.5% of patients, and mixed S. pneumoniae and atypical bacterial infections in 8.2% of children.…”
Section: Community-acquired Pneumoniamentioning
confidence: 92%
“…Studies have shown that the inclusion of a macrolide in treatment regimens can improve clinical outcome in children with lower RTIs due to atypical pathogens [65], including those with CAP [66], in whom it is especially difficult to determine the microbial aetiology.…”
Section: Community-acquired Pneumoniamentioning
confidence: 99%
“…Each acute and convalescent serum sample was tested after absorption for IgM and IgG antibodies to M. pneumoniae (ELISA; Pantec), and IgM, IgA and IgG antibodies to C. pneumoniae (microimmunofluorescence; Labsystems) as described previously (Wang & Grayston, 1970;Esposito et al, 2002a). Nasopharyngeal aspirates were evaluated for the presence of M. pneumoniae and C. pneumoniae DNA by using validated nested PCR for both pathogens, as described previously (Tong & Sillis, 1993;Abele-Horn et al, 1998;Blasi et al, 1999;Esposito et al, 2002a).…”
Section: Methodsmentioning
confidence: 99%
“…Each acute and convalescent serum sample was tested after absorption for IgM and IgG antibodies to M. pneumoniae (ELISA; Pantec), and IgM, IgA and IgG antibodies to C. pneumoniae (microimmunofluorescence; Labsystems) as described previously (Wang & Grayston, 1970;Esposito et al, 2002a). Nasopharyngeal aspirates were evaluated for the presence of M. pneumoniae and C. pneumoniae DNA by using validated nested PCR for both pathogens, as described previously (Tong & Sillis, 1993;Abele-Horn et al, 1998;Blasi et al, 1999;Esposito et al, 2002a).The nested PCR technique for M. pneumoniae was developed by AbeleHorn et al (1998), and that for C. pneumoniae by Tong & Sillis (1993); both techniques have been found to correlate well with cultures (Tong & Sillis, 1993; Abele-Horn et al, 1998). To avoid risk of contamination, sample preparation, PCR amplification and product analysis were performed in separate rooms.…”
mentioning
confidence: 99%
“…The evidence indicates that clinical and radiological findings cannot be used to reliably discriminate between CAP of viral, bacterial or atypical aetiology [169,170]. Rapid isolation of bacterial pathogens and the prescription of appropriate narrow-spectrum antibiotics are not feasible in most circumstances.…”
Section: Current Unlicensed and Off-label Usementioning
confidence: 99%